DESORPTION OF GOLD AND SILVER FROM ACTIVATED CARBON - Lili Tahli; Tatang Wahyudi (Indonesian Mining Journal, 2017)
Experiments of gold and silver elution were conducted using several parameters, either fixed or varying parameters. Ethanol volume, temperature and percent solid belonged to varying parameters while loaded carbon, stirring rate, concentrations of NaOH and NaCN served as fixed parameters. The experiment results showed that the optimum condition for such a process included 20% of ethanol volume, 80°C of temperature and solid fraction of 25%. Using such condition, the experiment was conducted for 10-hour contact time and yielded the highest desorption percentages for gold and silver, namely 80.10 and 70.73% respectively. The derived contents of gold and silver were 295.16 and 159.38 ppm while their achieved weights were 56.080 and 30.601 µ g. The fact that the achieved contents of gold and silver was close to the requirements for electrowinning process, it is suggested that the next process using a semi-continue one in terms of gaining a result that satisfies the requirement for electrowinning.